Pembiayaan Musyarakah di Bait Al-Mal Wa At-Tamwil (BMT) An-Nur Rewwin Waru Sidoarjo - Nur Afrida; Nur Lailatul Musyafa’ah (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2018)
This article discusses musyarakah financing at BMT An-Nur Rewwin Waru Sidoarjo in the perspective of Islamic law. This research is field research and qualitative. Data were collected through observation, interview, and documentation techniques. The data analyzed using a descriptive analysis method with an inductive mindset describes the general description of musyarakah financing at BMT An-Nur Rewwin first, then analyzed with the concept of musyarakah in the DSN-MUI fatwa number 08/DSN-MUI/ IV/2000 concerning Musyarakah Financing. This study concludes that the musyarakah financing at BMT An-Nur is done using the customer registering at the administration and filling out the registration form with the designation of a business. It can be disbursed after being approved by the director. In reality, the customer uses the loan not for business as in the application, but the funds are used for consumptive needs. In the perspective of Islamic law, the Musyarakah financing at BMT An-Nur Rewwin in terms of the legal contract is valid because it meets the requirements and pillars contained in the Fatwa of DSN-MUI number 08/DSN-MUI/IV/2000 concerning Musyarakah Financing. However, it was canceled because it was wrong. one party misuses the allotted loan funds. In line with the conclusions above, it is recommended that BMT An-Nur Rewwin tighten supervision on the use of funds by customers to avoid misuse. For customers, they should be more trustworthy in the use of loan funds for business.